2009
DOI: 10.1590/s0103-50532009000300023
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient and general method for the preparation of (Z)-allylic bromides derived from Morita-Baylis-Hillman adducts

Abstract: (Z)-2-(Bromometil)-2-alcenoatos são importantes intermediários sintéticos e foram preparados de forma simples e prática pelo tratamento de α-metileno-β-hidroxiésteres (produtos da reação de Morita-Baylis-Hillman) com LiBr/H 2 SO 4 em acetonitrila à temperatura ambiente. Além de fornecer altos rendimentos e de tolerar a presença de diversos grupos funcionais, esta nova metodologia utiliza reagentes baratos e não faz uso de HBr.Representative (Z)-2-(bromomethyl)-2-alkenoates were easily prepared in high yield by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The synthesis of the target allylic selenocyanates 1 a–g was efficiently achieved by combining the nucleophilic potassium selenocyanide (KSeCN) with the electrophilic allylic bromide 2 a–g (Scheme, Table ), a versatile precursor readily prepared through the treatment of Morita‐Baylis‐Hillman adducts with LiBr in acidic medium . The novel allylic selenocyanates 1 a–g were obtained in high yield and elevated purity, and were fully characterized by spectroscopic methods.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the target allylic selenocyanates 1 a–g was efficiently achieved by combining the nucleophilic potassium selenocyanide (KSeCN) with the electrophilic allylic bromide 2 a–g (Scheme, Table ), a versatile precursor readily prepared through the treatment of Morita‐Baylis‐Hillman adducts with LiBr in acidic medium . The novel allylic selenocyanates 1 a–g were obtained in high yield and elevated purity, and were fully characterized by spectroscopic methods.…”
Section: Resultsmentioning
confidence: 99%
“…During the development of a simple and general method to prepare ( Z )‐allylic bromides22 by treating 1 with a combination of lithium bromide and sulfuric acid in acetonitrile at room temp.,23 we found that acetamides 2 and 3 (obtained from a Ritter type16,2427 reaction with the solvent) were competitively formed when LiBr was replaced by less soluble sodium or potassium bromide. Our interest in synthetic transformations involving allylic alcohols B 28 and in mechanistic studies on nucleophilic reactions29 prompted us to undertake an in‐depth investigation of the acid‐mediated solvolytic nucleophilic substitution reaction involving the α‐methylene‐β‐hydroxy esters 1 with acetonitrile to give the corresponding mixture of allylic acetamides 2 and 3 (Scheme ).…”
Section: Introductionmentioning
confidence: 85%
“…The preparation of the required isothiouronium salts 3 was readily achieved by combining a variety of N ‐substituted thioureas 4 with the 4‐nitroaryl‐substituted allylic bromide 5 a (which was obtained in high yield by treating the corresponding α‐methylene‐β‐hydroxyester with LiBr/H 2 SO 4 )8 in acetonitrile at rt in 66–97 % yield (Scheme ). Subsequent base‐mediated acetylation of N ‐substituted salts 3 a–d using acetic anhydride under a biphasic medium furnished the expected products as a mixture of monoacetylated isothioureas,6b with the N ‐acetyl‐ N′ ‐substituted isomers 1 a–d being the major products.…”
Section: Methodsmentioning
confidence: 99%